Copy Number Variation of Mitochondrial DNA Genes in Pneumocystis jirovecii According to the Fungal Load in BAL Specimens - Valero, Clara; Buitrago, María José; Gits-Muselli, Maud; Benazra, Marion; Sturny-Leclère, Aude; Hamane, Samia; Guigue, Nicolas; Bretagne, Stéphane; Alanio, Alexandre (Frontiers in Microbiology, 2016)
Abstract Pneumocystis jirovecii is an unculturable fungus and the causative agent of Pneumocystis pneumonia, a life-threatening opportunistic infection. Although molecular diagnosis is often based on the mtLSU rRNA mitochondrial gene due to its greater sensitivity, physiology and the dynamics of the mitochondria in this fungus remains largely unknown. We developed and optimized six real-time PCR assays in order to determine the copy number of four mitochondrial genes (mtSSU rRNA, mtLSU rRNA, NAD1 and CYTB) in comparison to nuclear genome (DHPS and HSP70) and tested 84 bronchoalveolar fluids of patients at different stages of the infection. Unexpectedly, we found that copy number of mitochondrial genes varied from gene to gene with mtSSU rRNA gene being more represented (37 copies) than NAD1 (23 copies), mtLSU rRNA (15 copies) and CYTB (6 copies) genes compared to nuclear genome. Hierarchical clustering analysis (HCA) allowed us to define five major clusters, significantly associated with fungal load (p=0.029), in which copy number of mitochondrial genes was significantly different among them. More importantly, copy number of mtLSU rRNA, NAD1 and CYTB but not mtSSU rRNA differed according to P. jirovecii physiological state with a decreased number of copies when the fungal load is low. This suggests the existence of a mixture of various subspecies of mtDNA that can harbor different amplification rates. Overall, we revealed here an unexpected plasticity and dynamics of P. jirovecii mitochondrial DNA that vary according to P. jirovecii’s physiological state.